Natural Coumarin Derivatives Activating Nrf2 Signaling Pathway as Lead Compounds for the Design and Synthesis of Intestinal Anti-Inflammatory Drugs - Luiz C. Di Stasi (MDPI AG, 2023)
Nrf2 (nuclear factor erythroid 2-related factor 2) is a transcription factor related to stress response and cellular homeostasis that plays a key role in maintaining the redox system. The imbalance of the redox system is a triggering factor for the initiation and progression of non-communicable diseases (NCDs), including Inflammatory Bowel Disease (IBD). Nrf2 and its inhibitor Kelch-like ECH-associated protein 1 (Keap1) are the main regulators of oxidative stress and their activation has been recognized as a promising strategy for the treatment or prevention of several acute and chronic diseases. Moreover, activation of Nrf2/keap signaling pathway promotes inhibition of NF-κB, a transcriptional factor related to pro-inflammatory cytokines expression, synchronically promoting an anti-inflammatory response. Several natural coumarins have been reported as potent antioxidant and intestinal anti-inflammatory compounds, acting by different mechanisms, mainly as a modulator of Nrf2/keap signaling pathway. Based on in vivo and in vitro studies, this review focuses on the natural coumarins obtained from both plant products and fermentative processes of food plants by gut microbiota, which activate Nrf2/keap signaling pathway and produce intestinal anti-inflammatory activity. Although gut metabolites urolithin A and urolithin B as well as other plant-derived coumarins display intestinal anti-inflammatory activity modulating Nrf2 signaling pathway, in vitro and in vivo studies are necessary for better pharmacological characterization and evaluation of their potential as lead compounds. Esculetin, 4-methylesculetin, daphnetin, osthole, and imperatorin are the most promising coumarin derivatives as lead compounds for the design and synthesis of Nrf2 activators with intestinal anti-inflammatory activity. However, further structure-activity relationships studies with coumarin derivatives in experimental models of intestinal inflammation and subsequent clinical trials in health and disease volunteers are essential to determine the efficacy and safety in IBD patients.